1977
DOI: 10.1111/j.1651-2227.1977.tb07931.x
|View full text |Cite
|
Sign up to set email alerts
|

The Foam Stability Test on Gastric Aspirate in the Prediction of Respiratory Distress Syndrome

Abstract: To evaluate the usefulness of the foam stability test (FST) on gastric aspirate for predicting respiratory distress syndrome (RDS) in premature infants, samples were collected at delivery or within 30 min from 194 infants less than or equal to 36 weeks gestation. Of 123 samples adequate for complete testing, 44 were positive at 1 : 2 dilution, 43 were positive only at dilutions less than 1 : 2 and 36 were negative at all dilutions. RDS was found in 2%, 21% and 25% of each group respectively. The FST on gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The present study confirms the inaccuracy of the shake test in predicting IRDS as reflected by a large number of false-positive results. 7,8,20,23,24 The disadvantage of the shake test is the interpretation of the intermediate group. Our study showed that no infant in this group developed IRDS, whereas Clements et al found 8 of 13 cases with intermediate test results had mild to severe IRDS.…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirms the inaccuracy of the shake test in predicting IRDS as reflected by a large number of false-positive results. 7,8,20,23,24 The disadvantage of the shake test is the interpretation of the intermediate group. Our study showed that no infant in this group developed IRDS, whereas Clements et al found 8 of 13 cases with intermediate test results had mild to severe IRDS.…”
Section: Discussionmentioning
confidence: 99%